Pelatihan Guru yang Tergabung dalam MGMP Matematika SMK se-Kabupaten Mojokerto dalam Implementasi PjBL untuk Mendukung Motivasi Belajar Siswa - Deka Anjariyah; Feriyanto Feriyanto (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
This study aims to increase teachers' knowledge about the Application of the Project Based Learning (PjBL) Model in learning mathematics so that it can support teachers' skills in preparing PjBL learning tools that motivate student learning. In this PKM activity, training and mentoring are collected in the preparation, implementation, and evaluation stages. The instruments used are observation sheets, questionnaire sheets, and training modules. Data analysis of this activity is descriptive qualitative. The results of the study show that training and mentoring activities for the implementation of the PjBL Model make a good contribution to increasing mastery of the material and increasing the ability of teachers to design PjBL learning tools that motivate student learning.